Кіоткські свята і народний календар - Ооморі Кейко (Народна творчість та етнографія, 2009)
Holidays and ceremonies of calendar cycle in the Kyoto region and other localities of Japan are characterized in the article. The population of Kyoto adhered to the ancient ceremonies long enough, due to influential Buddhist and Shinto monks. The author repeats over and over again, that in a city culture the traditional ceremonial calendar disappears gradually, remaining the prerogative of temple’s celebrations.